Measuring The Feasibility Of Catfish Farming Business - Nurhidayati Nurhidayati; Sujito Sujito; Rosyati Rosyati (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to determine the business feasibility of Pak Dayat's catfish farming, the feasibility of the business from the aspect located in RW VI, Bulusan Village, Tembalang District, Semarang. The study was conducted in June 2024 with data collection techniques in the form of observation, interviews, and documentation. The analysis tools used for the financial aspect use Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), Average Rate of Return (ARR), Profitability Index (PI), The results of the study are that the Payback Period of the business is more than 2 years and 3 months. it can be concluded that when viewed from the Payback Period, the catfish farming business is declared feasible to run. The NPV analysis produces a value greater than 0. Thus, when viewed from the NPV value, the catfish farming business is feasible to run. The results of the study obtained an IRR value greater than the desired level of profit. Namely the IRR value of 67.5, thus the catfish farming business is declared feasible to run. The ARR value is 33% higher than the requirement, so it can be said that this business is feasible to run. The Profitability Index figure shows a figure of 2.96> 1, so it can be said that the catfish farming business is feasible to run.